2005
DOI: 10.1182/blood-2005-05-1800
|View full text |Cite
|
Sign up to set email alerts
|

JAK2 mutation 1849G>T is rare in acute leukemias but can be found in CMML, Philadelphia chromosome–negative CML, and megakaryocytic leukemia

Abstract: An activating 1849G>T mutation of JAK2 (Janus kinase 2) tyrosine kinase was recently described in chronic myeloproliferative disorders (MPDs). Its role in other hematologic neoplasms is unclear. We developed a quantitative pyrosequencing assay and analyzed 374 samples of hematologic neoplasms. The mutation was frequent in polycythemia vera (PV) (86%) and myelofibrosis (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
278
3
10

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 348 publications
(305 citation statements)
references
References 19 publications
14
278
3
10
Order By: Relevance
“…24 Generalised pruritus was found more frequent in homozygous JAK2 mutated PV patients than unmutated or heterozygous mutated PV patients. 24,25 There are few data about relation of JAK2 mutation to leukemic transformation. Kraloyics et al were found no relationship for JAK2 mutation and leukemic transformation in 244 MPD patients.…”
Section: Introductionmentioning
confidence: 99%
“…24 Generalised pruritus was found more frequent in homozygous JAK2 mutated PV patients than unmutated or heterozygous mutated PV patients. 24,25 There are few data about relation of JAK2 mutation to leukemic transformation. Kraloyics et al were found no relationship for JAK2 mutation and leukemic transformation in 244 MPD patients.…”
Section: Introductionmentioning
confidence: 99%
“…However, leukemic transformation after such OLT has rarely been reported [6]. In our case, the progression to leukemia was rapid, which was highly unusual for ET [7], particularly with minimal prior cytoreduction.…”
Section: Discussionmentioning
confidence: 53%
“…Other recent studies found a similar incidence of the V617F mutation: 0/17 (Jones et al, 2005), 5/90 (6%) , 2/39 (5%) (Jelinek et al, 2005), 4/222 (2%, three had preceding MPD) (Levine et al, 2005b), 1/152 (0.7%) (Frohling et al, 2006), and 2/112 (2%) (Lee et al, 2006). The V617F mutation in AML was initially found in FAB M6 (1/53) (Frohling et al, 2006) and FAB M7 (2/11) (Jelinek et al, 2005), while the FAB subtype of AML was not described in other reports. In the current study, this mutation was also found to be present in one out of 12 patients with AML M2 (8%): one of the four patients with t(8;21)(q22;q22).…”
Section: Lane 5)mentioning
confidence: 53%
“…Recent studies have shown the V617F mutation to be present in some cases of acute myeloid leukemia (AML), myelodysplastic syndrome (MDS) and chronic myelomonocytic leukemia (CMMoL) (Jelinek et al, 2005;Levine et al, 2005b). However, limited information is available to determine whether the mutation is specifically associated with myeloid neoplasms, and most of the studies are from Europe and North America.…”
mentioning
confidence: 99%